PROJECT-BASED LEARNING SEBAGAI UPAYA MENINGKATKAN KREATIVITAS MENULIS KARANGAN PENDEK BAHASA JEPANG - Neneng Sutjiati; Linna Meilia Rasiban (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
This research was motivated from the difficulty of students to develop their ideas in writing essay. Project-Based Learning (PBL) is an innovative approach to learning that teaches a multitude of strategies critical for success in the twenty-first century. Students drive their own learning through inquiry, as well as work collaboratively to research and create projects that reflect their knowledge. From gleaning new, viable technology skills, to becoming proficient communicators and advanced problem solvers, students benefit from this approach to instruction. From the results of beginning questionnaire distributed as much as 80% of students obtained difficulty developing story ideas into written form complete. The difficulty factor is influenced from the lack of time to develop ideas other than internal factors are mastery of vocabulary, sentence patterns mastery structure. This class of experimental research focused on improving the learning model essay writing intermediate level (Chuukyuu Sakubun) that has been done. The object of this study is the student level 2 semesters 4 Japanese Education Department with a sample of 25 respondents.The results showed that learning with Project-Based Learning techniques to help students develop their ideas and write a short essay in Japanese.